Prognostic significance of early alpha fetoprotein and des-gamma carboxy prothrombin responses in unresectable hepatocellular carcinoma patients undergoing triple combination therapy - Zhang, Teng; Li, Wengang; Chen, Qian; He, Weiping; Sun, Jing; Li, Dong; Wang, Quan; Duan, Xuezhang (Frontiers in Immunology, 2024)
BackgroundRecent advancements in combination therapy for unresectable hepatocellular carcinoma (uHCC) have shown promise, but reliable serological prognostic indicators are currently lacking for patients undergoing triple combination therapy of stereotactic body radiation therapy (SBRT), immunotherapy, and targeted therapy. We aimed to investigate the prognostic significance of early alpha fetoprotein (AFP) and des-gamma-carboxy prothrombin (DCP) responses in these patients.MethodsThis retrospective research included 115 uHCC patients treated with SBRT in combination with immunotherapy and targeted therapy (triple therapy) at our institution from April 2021 to December 2022. Participants were categorized into high AFP and high DCP cohorts based on baseline levels. AFP and DCP responses were defined as decreases from baseline of over 50% and 70%, respectively, according to ROC curve analysis. Differences in overall survival (OS), progression-free survival (PFS), and objective response rate (ORR) were assessed between the tumor biomarker response and non-response groups.ResultsMultivariate analysis indicated that AFP or DCP response at 6-8 weeks post-therapy significantly influenced ORR (high AFP cohort: odds ratio [OR] 5.50, 95% CI 2.04-14.83, p=0.001; high DCP cohort: OR 7.99, 95%CI 2.82-22.60, p<0.001). The median PFS was notably longer in tumor biomarker response groups (high AFP cohort: 13.7 vs 6.2 months, hazard ratio [HR] 0.36, 95% CI 0.20-0.62, p<0.001; high DCP cohort: 15.6 vs 9.3 months, HR 0.44, 95% CI 0.26-0.74, p=0.002). AFP or DCP response was associated with prolonged OS (high AFP cohort: not reached vs. 21.9 months, HR 0.47, 95% CI 0.22-0.99, p=0.047; high DCP cohort: not reached vs. 20.6 months, HR 0.35, 95% CI 0.14-0.86, p=0.022).ConclusionAFP or DCP response at 6-8 weeks post-therapy predicts better oncological outcomes in patients with uHCC treated with triple therapy.